Peningkatan Kualitas Kemandirian Dan Tanggung Jawab Belajar Siswa Dengan Mobile Seamless Learning - Rifqi Ghufron Maula; Hanifuddin Hanifuddin (Jurnal Ilmiah Wahana Pendidikan, 2022)
Naturally in the 21st century the world of education experiences an emphasis on the learning process. Information technology and its devices are always developing very rapidly. One of the impacts of this is the quality of independence and responsibility for students who can be better or vice versa. Coupled with the virus that has shocked the world, namely the Covid-19 virus, forcing education implementers to adapt to situations like this. This article is the result of the conversion of a thesis research which was researched by the researcher himself, it is hoped that it can be useful for readers and become a benchmark and reference for further research. Case study research is carried out with surveys as well as observations at the location in order to obtain the necessary data. The data collected is in the form of text or writing and converted images. Collecting data by conducting observations, interviews, and documentation. The results of the study were to determine the mobile seamless learning, independence, and responsibility of students, along with increasing student independence and responsibility at MAN 3 Jombang.